الفكر الإسلامي وتجلياته في الأدب الملايوي المعاصر: "تيتير ذيكير" (لحن الذكر) للشاعر كمالا نموذجا: Islamic Thought and it’s Manifestation in Contemporary Malay Literature: “Titir Zikir” by Poet Kemala as an Example - Mohamad Zainol, Nur Farhana; Ahmad H. Osman, Rahmah; Bohari, Khairunnisa; Mohammad Elssadoony, Abdallah Ehab (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص الفكر الإسلامي هو كل ما أنتجه عقل المسلمين في المعارف الكونية المتصلة بالله، والعالم، والإنسان.وبعبارة أخرى هو الذي يعبر عن اجتهادات العقل الإنساني؛ لتفسير تلك المعارف العامة في إطار المبادئ الإسلامية عقيدة، وشريعة، وسلوكا. وهو يُعرف كذلك بما أصدره المسلم أثناء تعامله مع النصوص الإسلامية وفق منهج علمي. وكمالا هو أحد الأدباء الملايويين الذين اهتموا اهتماماً كبيراً بالمبادئ والأفكار الإسلامية في أعمالهم الفنية؛ حيث تبلورت أفكاره الإسلامية في كثير من مؤلفاته، وانطلاقاً من هذا الأساس تسعى هذه الدراسة إلى إبراز عناصر الفكر الإسلامي التي ظهرت في ديوانه المسمى ب"تيتير ذيكير"، كما تحاول تسليط الضوء على آراء بعض الأدباء العرب والملايويين حول الأدب الإسلامي؛ لتبين لنا أن ديوان "تيتير ذيكير" يدخل ضمن الأدب الإسلامي، وقد اعتمدت الدراسة على المنهج الوصفي التحليلي؛ حيث تقوم على تحليل مضمون بعض الأشعار المختارة من الديوان المشار إليه، وتوصلت الدراسة إلى أن كمالا شاعر إسلامي يهتم بالفكر الإسلامي في كتاباته، ويتجلى هذا التصور الإسلامي في ديوانه "تيتير ذيكير" حيث تحدث عن محاسبة النفس والعلاقة الأسرية والموت والعدالة والرئاسة وشوق العباد لرب العباد، وكثير من التصورات الإسلامية الأخرى. Abstract Kemala is one of the Malay poets who concerns with the Islamic values in his literary work, and these Islamic values can be seen through many of his writings. Hence based on this basis, this study aimed to highlight these Islamic thoughts in his anthology named “Titir Zikir”, as well as highlighting the opinions of some Arab and Malay poets on the Islamic literature to conclude that the anthology "Titir Zikir" is classified as Islamic literature. The study relied on the descriptive analytical method, as it is analyzing the content of some selected poetry from the aforementioned anthology. The study concluded that Kemala himself is an Islamic poet who concerned with Islamic thought in his writing, and his Islamic messages are manifested in the anthology “Titir Zikir” where he talks about self-evaluation (Muhāsabah al-nafs), family relationship, death, justice, leadership, as well as the longing of the servants for his Lord, and many other messages related to the Islamic thought.